2018
DOI: 10.1089/bio.2018.0033
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Need: Linking Traits to Genebank Accessions

Abstract: Genebanks are responsible for collecting, maintaining, characterizing, documenting, and distributing plant genetic resources for research, education, and breeding purposes. The rationale for requests of plant materials varies highly from areas of anthropology, social science, small-holder farmers, the commercial sector, rehabilitation of degraded systems, all the way to crop improvement and basic research. Matching “the right” accessions to a particular request is not always a straightforward process especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 72 publications
0
37
0
1
Order By: Relevance
“…However, characterization of large number of accessions held in the global collections is resources consuming. Several solutions have been developed and tested to address this issue, including core collections, FIGS, and GWAS (Anglin et al, 2018). The performance of core collection and GWAS to link a trait of interest to a genebank accession has been evaluated (Anglin et al, 2018); however, the application of FIGS has yet not been examined for quantitative morphological traits such as grain traits.…”
Section: Variation and Prediction Accuracies For Wheat Landrace's Gramentioning
confidence: 99%
See 2 more Smart Citations
“…However, characterization of large number of accessions held in the global collections is resources consuming. Several solutions have been developed and tested to address this issue, including core collections, FIGS, and GWAS (Anglin et al, 2018). The performance of core collection and GWAS to link a trait of interest to a genebank accession has been evaluated (Anglin et al, 2018); however, the application of FIGS has yet not been examined for quantitative morphological traits such as grain traits.…”
Section: Variation and Prediction Accuracies For Wheat Landrace's Gramentioning
confidence: 99%
“…Several solutions have been developed and tested to address this issue, including core collections, FIGS, and GWAS (Anglin et al, 2018). The performance of core collection and GWAS to link a trait of interest to a genebank accession has been evaluated (Anglin et al, 2018); however, the application of FIGS has yet not been examined for quantitative morphological traits such as grain traits. In this research, we reported the efficiency of genome-wide prediction to predict the ICARDA genebank wheat landraces using highdensity DartSeq TM markers.…”
Section: Variation and Prediction Accuracies For Wheat Landrace's Gramentioning
confidence: 99%
See 1 more Smart Citation
“…Recent developments such as using passport data with digital object identifiers (DOI) on accessions and transactions [12], large-scale morphological characterization and phenotyping [13], and molecular studies with next-generation sequencing platforms [14][15][16][17][18] have all improved the possibilities to identify duplicates. Regardless of the approach, proper data and transparent genebank information systems are needed to facilitate duplication assessments [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is extremely necessary to explore new methodologies, tools and processes to support and improve crop production (Shunmugam et al 2018). Plant diseases, mainly caused by bacterial (Mansfield et al 2012), viral (Scholthof et al 2011) and fungal pathogens (Dean et al 2012), and parasitic nematodes (Jones et al 2013), are the main limiting factors of crop yields (Anglin et al 2018). For example, rice bacterial blight (BB) leads to leaf blight during the growing season, hindering photosynthesis and diminishing the production and quality of rice (Kim and Reinke 2019).…”
Section: Introductionmentioning
confidence: 99%